2007
DOI: 10.1097/fjc.0b013e31803e8772
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregometry and Receptor Binding to Predict the Magnitude of Antithrombotic and Bleeding Time Effects of Clopidogrel in Rabbits

Abstract: Target levels of ex vivo inhibition of platelet aggregation (IPA) induced by adenosine diphosphate (ADP) that produce clinically relevant effects of clopidogrel, a P2Y12 antagonist, are unclear. We examined standard and modified IPA and P2Y12 receptor occupancy as predictors of antithrombotic (% thrombus weight reduction) and bleeding time (BT, fold-increase over control) effects of clopidogrel in rabbit models of carotid artery thrombosis and cuticle bleeding, respectively. Standard and modified IPA with 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 26 publications
1
27
0
3
Order By: Relevance
“…For example, studies performed in rabbits suggest that unexplained bleeding occurs at levels of clopidogrel greater than those required to provide complete inhibition of platelet aggregation (Wong et al, 2009). In particular, high doses of clopidogrel providing limited incremental benefits in preventing arterial thrombosis have been associated with disproportionate levels of bleeding in both rabbits and rats Wong et al, 2007). Similar discrepancies have been reported in humans, with CYP2C19*2 carriers having a higher rate of thrombotic events but a rate of bleeding similar to those of noncarriers (Mega et al, 2009).…”
Section: Introductionmentioning
confidence: 53%
“…For example, studies performed in rabbits suggest that unexplained bleeding occurs at levels of clopidogrel greater than those required to provide complete inhibition of platelet aggregation (Wong et al, 2009). In particular, high doses of clopidogrel providing limited incremental benefits in preventing arterial thrombosis have been associated with disproportionate levels of bleeding in both rabbits and rats Wong et al, 2007). Similar discrepancies have been reported in humans, with CYP2C19*2 carriers having a higher rate of thrombotic events but a rate of bleeding similar to those of noncarriers (Mega et al, 2009).…”
Section: Introductionmentioning
confidence: 53%
“…We adopted the doses of cilostazol (100 mg/kg), aspirin (10 mg/kg), and clopidogrel (3 mg/kg) for our MCA occlusion study because this dose of cilostazol showed greatest inhibition, and these were the minimal effective doses for aspirin and clopidogrel. Higher dosages of aspirin and clopidogrel were not used to avoid an unnecessary risk of bleeding during the experiments (Clark et al, 1991;Wong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…the threshold dose that completely blocks ex vivo platelet aggregation response to arachidonic acid and serum production of thromboxane B 2 [12], and is thus comparable to the 81 mg clinical dose of aspirin [13]. We studied clopidogrel at 3 mg kg )1 day )1 per oral (p.o.…”
Section: Arterial Thrombosis Studiesmentioning
confidence: 99%
“…) was dosed orally once daily for three days as described previously [12]. Following the third oral dose of clopidogrel or vehicle, rabbits were anesthetized 0.5 h post-dose, i.v.…”
Section: Arterial Thrombosis Studiesmentioning
confidence: 99%
See 1 more Smart Citation